Performance and mechanism of ether-based binder (KH-PE) in electrochemically switched ion exchange lithium extraction from salt lake brine with high Mg/Li ratio - Tianyu Feng; Qian Xu; Beichen Sun; Yulong Zhang; Can Wang; Xiao Du; Yongguo Li; Fengfeng Gao; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2026)

In-situ passivation of Cu and Zn in dyeing sludge incineration ash: Neglected role of the sulfur cycle - Beichen Du; Yuting He; Qinyuan Zhang; Jianran Ye; Xiao Hu; Chuqi Ye; Yuchi Chen; Siwei Liu; Jia Hu; Teng Wang (Journal of Environmental Chemical Engineering, 2025)

LLTO-based electrodes for selective lithium extraction from high Mg2+/Li+ brines: Performance and mechanistic insights - Ran Zhang; Jialu Chen; Qian Xu; Beichen Sun; Xiao Du; Shanxia Luo; Xiaogang Hao (Journal of Environmental Chemical Engineering, 2025)

Temperature response of magnetic susceptibility and pore structure of white Bleached sandstone - Beichen Du; Jishi Geng; Qiang Sun; Xin Hu; Hao Huang; Pengda Ma; Pengfei Li (Journal of Applied Geophysics, 2025)

An Approach to Optimize the Efficiency of an Air Turbine of an Oscillating Water Column Based on Adaptive Model Predictive Control - Yan Huang; Weixun Dong; Jianyu Fan; Shaohui Yang; Zhichang Du; Yongqiang Tu; Chenglong Li; Beichen Lin (Journal of Marine Science and Engineering, 2025)
Wave energy, as a vast renewable resource, remains underutilized despite its high potential. The oscillating water column (OWC) is one of the most efficient way to harvest wave energy. Due to the randomness of ocean wave excitation, a control strategy is needed to keep the conversion efficiency of OWC at a certain level. In this paper, an adaptive model predictive control (AMPC) method is proposed to optimize the efficiency of the air turbine and improve the overall efficiency of the OWC. Experiments were conducted in a wave flume to obtain realistic wave data, which were fed into the AMPC model for simulations. Results indicate that AMPC-optimized turbine efficiency exhibits improved performance under regular wave conditions and significantly enhances efficiency within certain intervals under short-period irregular waves. However, as the wave period increases, optimization becomes less stable. Overall, the study concludes that the adaptive MPC model effectively optimizes turbine efficiency under most conditions, highlighting its potential for enhancing OWC performance.

Study of a Center Pipe Oscillating Column Wave Energy Converter Combined with a Triboelectric Nanogenerator Device - Yan Huang; Shaohui Yang; Jianyu Fan; Zhichang Du; Beichen Lin; Yongqiang Tu; Lei Pan (Journal of Marine Science and Engineering, 2024)
Wave energy is one of the most widely distributed and abundant energies in the ocean, and its conversion technology has been broadly researched. In this paper, a structure that combines a traditional center pipe oscillating water column and a triboelectric nanogenerator is proposed. Firstly, the structural characteristics and geometric parameters of the device are designed. The working process of the device is introduced, the motion equation of the device is established, and the power generation principle of the triboelectric nanogenerator is deduced and analyzed theoretically. Secondly, hydrodynamic modeling and simulation are carried out, the influence of the bottom shape of the main floating body and the structural parameters of the sag plate on the hydrodynamic force of the device is analyzed, and an electric field simulation of the generation process of the friction nanogenerator is carried out. Finally, experiments involving the wave water tank of the proposed device are conducted, including charging the capacitor of the device under different wave conditions and directly lighting the LED lamp. The performance of the proposed device under different wave conditions is discussed. According to the test results, the feasibility of the proposed device for wave energy conversion is confirmed.

Experimental Study of Desorption and Seepage Characteristics of Single Gas and CO2–CH4 Gas Mixture in Coal - Beichen Yu; Dongming Zhang; Bin Xu; Weijing Xiao; Chongyang Wang; Weihang Du (Natural Resources Research, 2022)